2015
DOI: 10.1038/sdata.2015.72
|View full text |Cite
|
Sign up to set email alerts
|

Species-wide genome sequence and nucleotide polymorphisms from the model allopolyploid plant Brassica napus

Abstract: Brassica napus (oilseed rape, canola) is one of the world’s most important sources of vegetable oil for human nutrition and biofuel, and also a model species for studies investigating the evolutionary consequences of polyploidisation. Strong bottlenecks during its recent origin from interspecific hybridisation, and subsequently through intensive artificial selection, have severely depleted the genetic diversity available for breeding. On the other hand, high-throughput genome profiling technologies today provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 28 publications
1
63
0
1
Order By: Relevance
“…Earlier studies also identified chromosome rearrangements within the established B. napus gene pool using molecular markers: genotype-specific translocations were detected through assessment of marker segregation patterns (Sharpe et al 1995;Osborn et al 2003). Nevertheless, it was not until next-generation sequencing technologies enabled large-scale genome resequencing that the true extent of such rearrangements in the B. napus germplasm pool and their implications for polyploid evolution, trait variation and breeding became apparent Schmutzer et al 2015). A clear example of a non-homologous chromosome exchange in B. napus directly impacting a trait was identified by Liu et al (2012): a translocation between A9 and C8 resulted in two copies of an A9 allele, affecting seed acid detergent lignin content (Fig.…”
Section: Molecular Marker Genotypingmentioning
confidence: 99%
“…Earlier studies also identified chromosome rearrangements within the established B. napus gene pool using molecular markers: genotype-specific translocations were detected through assessment of marker segregation patterns (Sharpe et al 1995;Osborn et al 2003). Nevertheless, it was not until next-generation sequencing technologies enabled large-scale genome resequencing that the true extent of such rearrangements in the B. napus germplasm pool and their implications for polyploid evolution, trait variation and breeding became apparent Schmutzer et al 2015). A clear example of a non-homologous chromosome exchange in B. napus directly impacting a trait was identified by Liu et al (2012): a translocation between A9 and C8 resulted in two copies of an A9 allele, affecting seed acid detergent lignin content (Fig.…”
Section: Molecular Marker Genotypingmentioning
confidence: 99%
“…Since then, a Brassica 60k SNP array has been used in combination with large association panels by several research teams to analyse the genetic basis of traits, including resistance against pathogens Hatzig et al 2015;Wu et al 2016). Resequencing of 52 diverse natural and synthetic B. napus accessions has resulted in identification of >4 million SNPs, which are being exploited for breeding using primary and secondary gene pools (Schmutzer et al 2015).…”
Section: Novel Genomic Approaches For Rapid Identification Of R Genesmentioning
confidence: 99%
“…Molecular markers provide the genetic tools needed for implementation, enable potentially exploitable genes to be located, and help elucidate the genetic mechanisms involved. Recent improvements in genome sequencing have enabled genome characterization, identification of structural rearrangements, and high-density linkage maps to be constructed for crop species, such as Brassica napus, which have large and complex genomes (2)(3)(4). Consequently, genome-wide association studies (GWAS) can now be conducted in crop species (5).…”
mentioning
confidence: 99%